Conformational diversity and the emergence of sequence signatures during evolution. (June 2015) - Parisi, Gustavo; Zea, Diego Javier; Monzon, Alexander Miguel; Marino-Buslje, Cristina
Highlights: Protein's native structure is an ensemble of conformers with similar energies. Conformational diversity constraints sequence divergence. High conformational diversity correlates with slow evolution. Residues coevolution networks form spatial clusters in the protein structure. Coevolutionary analysis captures residue–residue correlations within different conformations. Abstract : Proteins' native structure is an ensemble of conformers in equilibrium, including all their respective functional states and intermediates. The induced-fit first and the pre-equilibrium theories later, described how structural changes are required to explain the allosteric and cooperative behaviours in proteins, which are key to protein function. The conformational ensemble concept has become a key tool in explaining an endless list of essential protein properties such as function, enzyme and antibody promiscuity, signal transduction, protein–protein recognition, origin of diseases, origin of new protein functions, evolutionary rate and order–disorder transitions, among others. Conformational diversity is encoded by the amino acid sequence and such a signature can be evidenced through evolutionary studies as evolutionary rate, conservation and coevolution.